Isolation and Characterization of Nanocellulose from Rice Husk (Oryza sativa L.) Waste Through Chemical and Ultrasonication Treatment - Paramitha, Viona Witya; Maharani, Dina Kartika (Jurnal Pijar Mipa, 2025)
Rice husk waste is one of the abundant lignocellulosic biomass sources in Indonesia and holds significant potential as a raw material for nanocellulose production. This study aims to isolate nanocellulose from rice husk through a combination of chemical and mechanical treatments to obtain a product with high crystallinity and nanoscale particle size. The isolation process involved several steps: alkali treatment using NaOH to remove hemicellulose, bleaching with H2O2 to degrade lignin, and acid hydrolysis using H2SO4 to eliminate the amorphous regions of cellulose. The resulting cellulose suspension was then subjected to ultrasonic treatment to further reduce particle size and achieve a more homogeneous dispersion, followed by freeze drying to obtain stable dry nanocellulose powder. Characterization using Fourier Transform Infrared Spectroscopy (FTIR) revealed changes in chemical structure, marked by the disappearance of lignin and hemicellulose peaks and the dominance of hydroxyl (-OH) and C-O functional groups, indicating increased cellulose purity. The nanocellulose yield obtained from this process was 38.15%, calculated based on the dry weight of nanocellulose relative to the initial dry weight of rice husk used. This value falls within the typical range reported for nanocellulose isolation using sulfuric acid hydrolysis and suggests that the applied method was effective in converting rice husk biomass into nanocellulose. The relatively high yield also supports the viability of rice husk as a sustainable and cost-efficient raw material for nanocellulose production. These findings demonstrate that rice husk waste can be effectively converted into high-quality nanocellulose through combined chemical and mechanical approaches, offering a sustainable and value-added solution for various functional materials, biodegradable packaging, and polymer composite applications.